Invincible - Reed, Amy Lynn. (New York : Katherine Tegen Books, 2015)
Evie is living on borrowed time. She was diagnosed with terminal cancer several months ago and told that by now she'd be dead. Evie is grateful for every extra day she gets, but she knows that soon this disease will kill her. Until, miraculously, she may have a second chance to live. All Evie had wanted was her life back, but now that she has it, she feels like there's no place for her in it--at least, not for the girl she is now. Her friends and her parents still see her as Cancer Girl, and her boyfriend's constant, doting attention is suddenly nothing short of suffocating. Then Evie meets Marcus. She knows that he's trouble, but she can't help falling for him. Being near him makes her feel truly, fully alive. It's better than a drug. His kiss makes her feel invincible--but she may be at the beginning of the biggest free fall of her life.
Keywords: Cancer -- Patients -- Fiction; Cancer in children -- Fiction; Addicts -- Fiction; Teenage girls -- Fiction